Determination of the photoinduced birefringence and of the refractive index by Brewster method of epoxy resin doped with CdS - Silveira, J. B.; Reynoso, V. C. S.; Aquino, Hermes Adolfo de [UNESP]; Carvalho, C. L. [UNESP] (Elsevier B.V., 2012)
This work describes the synthesis of polymeric composites based on epoxy resin doped with different concentrations of cadmium sulfide (CdS). We studied the photoinduced birefringence and the refractive index by Brewster method as a function of the CdS concentration. UV-Vis spectroscopy was used to determine the absorption bands of the samples. An experimental arrangement to ascertain the photoinduced birefringence used a writing LASER (ion Ar+ of lambda = 457 nm) and a reading LASER (He-Ne of lambda = 632.8 nm). The results were quantified using the theoretical model purposed by Debye, where it was observed that the pure epoxy resin presented photoinduced birefringence, which increased with the addition of the CdS. Therefore, it was verified that the variation of the power of the writing LASER directly contributes to the amount of photoinduced birefringence. In addition, the behavior of the refractive index of the composite as a function of the addition of CdS was verified by the Brewster angle technique to provide a wavelength of 650 nm using a radiation source with a monochromator. We observed a linear increase in the refractive index with the addition of CdS. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Epoxy resin; CdS; Birefringence photoinduced; Brewster method